ANALISIS KARAKTER TANGGUNG JAWAB ANAK USIA SEKOLAH DASAR SELAMA PEMBELAJARAN DARING - Muhammad Akmal Abrori; Henry Suryo Bintoro; Sekar Dwi Ardianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to describe the process of implementing online learning for elementary school age children and to describe the character of responsibility of elementary school aged children during online learning. This research utilized qualitative research methods with the type of field research. Data were collected by conducting observations, interviews and documentation. Then, the data were analyzed through data reduction, data presentation, and drawing conclusions. The results showed that (1) The learning process at one of elementary schools in Kecamatan Kaliwungu was carried out quite well because the teacher provided materials and assignments by utilizing Android assisted media such as Whatsapp. (2) It appeared that students were already good at carrying out several aspects of the responsibility indicator such as carrying out the duty, doing according to instructions, carrying out tasks according to theability, submitting assignments on time, being responsible for every deeds, and perform tasks based on the results of his own work. The benefits of this research were (1) it enriched references to the world of education, especially in terms of assessing the character of responsibility in students, and (2) it enriched the scientific repertoire in the field of theoretical education regarding the implementation of online learning during the Covid-19 pandemic and it could be used as a reference for theoretical studies to find out and understand the research context.